Medications and Recent Patents for Status Asthmaticus in Children - Lun E. Hon, Kam; Leung, Alexander K.C. (Recent Patents on Inflammation & Allergy Drug Discovery, 2017)
Background: Status asthmaticus is an acute exacerbation of asthma that is persistent and intractable and remains unresponsive to initial treatment with bronchodilators and systemic corticosteroids and that the condition can result in hypoxemia, hypercarbia, and secondary respiratory failure. Objective: To review treatment and recent patents on management of status asthmaticus. Method: A PubMed search was completed in Clinical Queries using the key term status asthmaticus
Keywords: Anti-IgE antibody